SARS‐CoV‐2 testing and outcomes in the first 30 days after the first case of COVID‐19 at an Australian children's hospital. (23rd June 2020) - Ibrahim, Laila F; Tosif, Shidan; McNab, Sarah; Hall, Samantha; Lee, Hyun Jung; Lewena, Stuart; Daley, Andrew J; Crawford, Nigel W; Steer, Andrew C; Bryant, Penelope A; Babl, Franz E
Abstract: Objective: International studies describing COVID‐19 in children have shown low proportions of paediatric cases and generally a mild clinical course. We aimed to present early data on children tested for SARS‐CoV‐2 at a large Australian tertiary children's hospital according to the state health department guidelines, which varied over time. Methods: We conducted a retrospective cohort study at The Royal Children's Hospital, Melbourne, Australia. It included all paediatric patients (aged 0–18 years) who presented to the ED or the Respiratory Infection Clinic (RIC) and were tested for SARS‐CoV‐2. The 30‐day study period commenced after the first confirmed positive case was detected at the hospital on 21 March 2020, until 19 April 2020. We recorded epidemiological and clinical data. Results: There were 433 patients in whom SARS‐CoV‐2 testing was performed in ED (331 [76%]) or RIC (102 [24%]). There were four (0.9%) who had positive SARS‐CoV‐2 detected, none of whom were admitted to hospital or developed severe disease. Of these SARS‐CoV‐2 positive patients, 1/4 (25%) had a comorbidity, which was asthma. Of the SARS‐CoV‐2 negative patients, 196/429 (46%) had comorbidities. Risk factors for COVID‐19 were identified in 4/4 SARS‐CoV‐2 positive patients and 47/429 (11%) SARS‐CoV‐2 negative patients. Conclusion: Our study identified a very low rate of SARS‐CoV‐2 positive cases in children presenting to a tertiary ED or RIC, none of whom were admitted to hospital. A high proportion of patients who were SARS‐CoV‐2 negative had comorbidities. Abstract : In this initial paediatric study of COVID‐19 to emerge from Australia, over a 30‐day period, the proportion of positive cases among those tested since our first positive case was very low at 4/433 (0.9%). None of the COVID‐19 patients were admitted and all recovered in the community. A high proportion of the SARS‐CoV‐2 negative patients (125/429 [46%]) had comorbidities.